Total morphosynthesis of biomimetic prismatic-type CaCO3 thin films. Issue 1 (December 2017) - Xiao, Chuanlian; Li, Ming; Wang, Bingjun; Liu, Ming-Feng; Shao, Changyu; Pan, Haihua; Lu, Yong; Xu, Bin-Bin; Li, Siwei; Zhan, Da; Jiang, Yuan; Tang, Ruikang; et al.
Abstract Biomimetic mineralization can lead to advanced crystalline composites with common chemicals under ambient conditions. An exceptional example is biomimetic nacre with its superior fracture toughness. The synthesis of the prismatic layer with stiffness and wear resistance nonetheless remains an elusive goal. Herein, we apply a biomimetic mineralization method to grow prismatic-type CaCO3 thin films, mimicking their biogenic counterparts found in mollusk shells with a three-step pathway: coating a polymer substrate, deposition of a granular transition layer, and mineralization of a prismatic overlayer. The synthetic prismatic overlayers exhibit structural similarity and comparable hardness and Young's modulus to their biogenic counterparts. Furthermore, employment of a biomacromolecular soluble additive, silk fibroin, in fabrication of the prismatic thin films leads to micro-/nano-textures with enhanced toughness and emerging under-water superoleophobicity. This study highlights the crucial role of the granular transition layer in promoting competition growth of the prismatic layer. The exterior layers of mollusk shells are prismatic in nature, endowing them with stiffness and wear resistance. Inspired by these biominerals, here, Jiang and colleagues grow structurally similar prismatic-type CaCO3 thin films with comparable stiffness and hardness.